2023
DOI: 10.37796/2211-8039.1406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-Retroviral Therapy on Baseline Serum Interleukin-18 levels in HIV-I Infected Patients Relative to Viral Suppression and CD4+ Gain: a prospective pilot study

Abstract: Background In HIV infection, dysregulation of cytokines, including interleukin 18 (IL-18), has been linked to poor clinical outcomes in studies mainly conducted in resource-rich countries. This phenomenon has not been well-studied in resource-limited settings where outcomes could be confounded by exposure to endemic infections and genetic factors. Objectives Therefore, the influence of immunological and virological status of HIV-infected, antiretroviral therapy (ART)-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…This finding diverges from studies elsewhere that reported profound resolution of cytopenia following ART treatment [ 21 27 33 ]. Despite previous indications that retroviral therapy is associated with reduced cytopenia incidence and severity due to ART-related attenuation of disease progression, as measured by CD4+ T cell count [ 26 ], our findings reveal a limited correlation of cART24 with decreased HGB concentration in participants with CD4+ T cell counts <200 cells/mm 3 . Notably, HGB concentration, the diagnostic marker for anemia, exhibited a robust negative correlation among participants with CD4+ T-lymphocyte counts above 200 cells/mm 3 , potentially linked to the use of integrase enzyme inhibitor, DTG.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This finding diverges from studies elsewhere that reported profound resolution of cytopenia following ART treatment [ 21 27 33 ]. Despite previous indications that retroviral therapy is associated with reduced cytopenia incidence and severity due to ART-related attenuation of disease progression, as measured by CD4+ T cell count [ 26 ], our findings reveal a limited correlation of cART24 with decreased HGB concentration in participants with CD4+ T cell counts <200 cells/mm 3 . Notably, HGB concentration, the diagnostic marker for anemia, exhibited a robust negative correlation among participants with CD4+ T-lymphocyte counts above 200 cells/mm 3 , potentially linked to the use of integrase enzyme inhibitor, DTG.…”
Section: Discussioncontrasting
confidence: 99%
“…In 2018, the WHO recommended transitioning to DTG-based antiretroviral therapy due to compelling evidence showcasing its rapid reduction of HIV viremia. However, this rapid viral reduction itself poses an independent risk factor for the development of immune reconstitution inflammatory syndrome (IRIS), characterized by paradoxical inadequate immune function recovery [ 34 35 ], as also suggested in our previous reports [ 25 26 ]. Furthermore, DTG triggers cell shrinkage and phospholipid scrambling of the erythrocyte cell membrane, a phenomenon known as eryptosis [ 34 ].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations